CORPORATE GOVERNANCE, ENTERPRISE RISK MANAGEMENT DAN NILAI PERUSAHAAN - Husaini, Husaini; Rafika, Indah (UNIB Press, 2014)
Implementation of the Good Corporate Governance (GCG) become a necessity in the business as a barometer of a company's accountability, while Enterprise Risk Management ERM) is inseparable from the practice of good corporate governance as a whole, which ultimately is expected to create value for the company on an ongoing basis. The purpose of this study was to examine the effect of the implementation of good corporate governance variables include the independent board, board size, audit committees, and the reputation of auditors and the implementation of ERM on firm value. Sample of this study was selected by exploring purposive sampling method. The sample of this study consists of 20 companies with the observation period of three (3) years (60 observations). The findings of this study showed that the independent board positively and significantly affect firm value. This result indicates that the greater proportion of independent member on board of the company, then the monitoring function could be improved and the lower the likelihood of conflict, so that the company's value increased. This study can not provide an empirical evidence on the impact of the board size and the audit committee on firm value. However, this found the the negative relationship between auditor's reputation and firm value. Interm of ERM, this study ound that there is a postive relationship between ERM implementation and firm value. It means that ERM implementations are used as part of overall corporate strategy, which allows companies to make better decisions and adjusted with acceptable risk, thus ultimately enhance shareholder value.